Membina keterangan: Pemeriksaan utama sebagai titik permulaan - Noraini Ibrahim, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2008)
The crux of an adversarial system as practiced in Malaysian courts is the adducing of evidence through the oral tradition. This usually involves examinations in three stages. A direct examination is conducted by the party that initiates the action, while a cross examination is carried out by the opposing side. In the event where a re-examination is necessary, the initiating party can re-examine his witness to ‘repair’ the damage done during the cross-examination. Institutionalized courtroom questioning involves questions posed by the lawyers with the answers to be provided for by the witnesses. Through strategic questioning therefore, a witness summoned to court by a litigating party will establish and then strengthen the version of the party that summon him. This paper is based on a case study of a criminal case observed at the Kuala Lumpur Criminal High Court 1, will delineate and then discuss several strategies employed by a counsel during the direct examination of an expert witness, in his effort to build a narrative that is both credible and believable